2009
DOI: 10.4014/jmb.0905.05036
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Mechanism of Novel Inhibitors of UDP-N-Acetylglucosamine Enolpyruvyl Transferase from Haemophilus influenzae

Abstract: Bacterial UDP-N-acetylglucosamine enolpyruvyl transferase (MurA) catalyzes the transfer of enolpyruvate from phosphoenolpyruvate (PEP) to uridine diphospho-Nacetylglucosamine (UNAG), which is the first step of bacterial cell wall synthesis. We identified thimerosal, thiram, and ebselen as effective inhibitors of Haemophilus influenzae MurA by screening a chemical library that consisted of a wide range of bioactive compounds. When MurA was preincubated with these inhibitors, their 50% inhibitory concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…However, the pattern of the proteins changes in the positive control and the three treated sample groups were different. Thimerosal’s anti-microbial action is dependent on it breaking down and releasing ethyl-mercury to penetrate the cell membranes and binds to intracellular enzymes, which then inhibits them and causes cell death [20]. Interestingly, previous studies have shown that some anti-bacterial drugs, such as aminoglycosides, tetracyclines and macrolides, exhibit inhibitory activity against P. insidiosum , but the MICs are incompatible with safe plasma levels [21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…However, the pattern of the proteins changes in the positive control and the three treated sample groups were different. Thimerosal’s anti-microbial action is dependent on it breaking down and releasing ethyl-mercury to penetrate the cell membranes and binds to intracellular enzymes, which then inhibits them and causes cell death [20]. Interestingly, previous studies have shown that some anti-bacterial drugs, such as aminoglycosides, tetracyclines and macrolides, exhibit inhibitory activity against P. insidiosum , but the MICs are incompatible with safe plasma levels [21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…A number of natural and synthetic MurA inhibitors were discovered in the past few years through structure–activity relationship experimentation and high‐throughput screening efforts . Interestingly, they present different modes of inhibition: covalent and non‐covalent binding within the active site, or blocking of the transition from the open to the closed form, which is required for catalysis . Although efficient in vitro , most compounds appeared to have no or weak antibacterial activity, and/or were not specific to MurA.…”
Section: Resistance To Antibiotics That Target Cytoplasmic Stepsmentioning
confidence: 99%
“…Screening campaigns to identify MurA inhibitors (Figure ) have been performed by various groups and led to the discovery of several low micromolar inhibitors including avenaciolides (I), tulipalines (II), the sesquiterpene lactone cnicin (III), , the cyclic disulfide RWJ-3981 (IV), and ebselen (V) . These inhibitors usually possess highly electrophilic moieties that target MurA by irreversible interactions in its active site through several mechanisms ranging from reaction of the key Cys residue in a Michael addition such as in the case of I and II (avenaciolides and tulipalines, respectively) ,, to the formation of a suicide inhibitor of the MurA active site via covalent binding to UNAG with III (cnicin). , V (ebselen) targets MurA through covalent binding to the active-site Cys key residue, and IV (RWJ-3981) acts by irreversible noncovalent attachment near the PEP binding site. , While targeting the catalytic Cys residue in the active site results in effective inhibition of MurA, this mechanism also implies that most of these compounds are inactive against the naturally occurring MurA C115D mutant. ,,, In addition, several of these inhibitors have been shown to react nonspecifically with thiol-containing compounds such as dithiothreitol (DTT) and also the cellular antioxidant glutathione (GSH). ,,, Moreover, the highly electrophilic structures also raise concerns about their specificity and safety as they have been shown to undergo several off-target interactions such as the inhibition of glutamate transport in rat liver mitochondria (III, avenaciolides) and the nonspecific inhibition of several bacterial targets in addition to failing to protect mice from death in a lethal Staphylococcus aureus (S. aureus) infection model (IV, RWJ-3981) .…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Screening campaigns to identify MurA inhibitors (Figure 2) have been performed by various groups and led to the discovery of several low micromolar inhibitors including avenaciolides (I), 20 tulipalines (II), 31 the sesquiterpene lactone cnicin (III), 32,33 the cyclic disulfide RWJ-3981 (IV), 34 and ebselen (V). 35 These inhibitors usually possess highly electrophilic moieties that target MurA by irreversible interactions in its active site through several mechanisms ranging from reaction of the key Cys residue in a Michael addition such as in the case of I and II (avenaciolides and tulipalines, respectively) 20,31,36 to the formation of a suicide inhibitor of the MurA active site via covalent binding to UNAG with III (cnicin). 32,33 V (ebselen) targets MurA through covalent binding to the active-site Cys key residue, 35 and IV (RWJ-3981) acts by irreversible noncovalent attachment near the PEP binding site.…”
Section: ■ Introductionmentioning
confidence: 99%